Millennial stocks and fluxes of large woody debris in lakes of the North American taiga - Gennaretti, Fabio; Arsenault, Dominique; Bégin, Yves (Journal of Ecology, 2014)
Summary : 1. Large woody debris (LWD) is an important cross-boundary subsidy that enhances the productivity of lake ecosystems and the stability of aquatic food webs. LWD may also be an important carbon sink because LWD pieces are preserved for centuries in the littoral zone of lakes and rivers. However, a long-term analysis of LWD stocks and fluxes in lakes, coupled with the reconstruction of past disturbances at the site level, has never been attempted. 2. Large woody debris was sampled in five lakes of the Quebec taiga. Actual LWD stocks were described and residence time of the LWD pieces was established using tree-ring and radiocarbon dating. LWD losses by decomposition and burial and other factors influencing LWD residence time were investigated using linear regressions. 3. Impacts of wildfires on LWD fluxes during the last 1400 years were reconstructed separately for the five lakes using piecewise regression models. Fire years at each site were identified from the recruitment dates of charred LWD pieces. 4. Large woody debris volume ranged between 0.92 and 1.57 m3 per 100 m of shoreline, and extrapolating these results to the landscape scale, it was concluded that LWD littoral carbon pools represent a minimal portion of boreal carbon storage. 5. Large woody debris residence time in boreal lakes was confirmed to be very long. Tree-ring dates of 1571 LWD pieces, mainly black spruce (Picea mariana (Mill.) BSP.), spanned the last 1400 years, while LWD specimens of older floating chronologies were preserved from decomposition for up to five millennia. The most influential variables explaining the variation in LWD residence time were the degree of burial and the distance from the shore. 6. Large woody debris recruitment rates averaged 5.8 pieces per century per 100 m of shoreline. Fourteen wildfires were the primary cause for changes in the rates of tree establishment in the riparian forests and of LWD recruitment in the lakes. 7. Synthesis. Interactions between terrestrial and aquatic ecosystems in northern ...